Effects of Nursing Quality Improvement on Thrombolytic Therapy for Acute Ischemic Stroke - Liu, Zhuo; Zhao, Yingkai; Liu, Dandan; Guo, Zhen-Ni; Jin, Hang; Sun, Xin; Yang, Yi; Sun, Huijie; Yan, Xiuli (Frontiers in Neurology, 2018)
Background and purpose: Intravenous thrombolytic therapy significantly improves the outcomes of acute ischemic stroke patients in a time-dependent manner. The aim of this study was to investigate whether continuous nursing quality improvement in stroke nurses has a positive effect on reducing the time to thrombolysis in acute ischemic stroke. Methods: The implementation of nursing quality improvement measures including establishing full-time stroke nurses, pre-notification by emergency medical services (EMS)，stroke team notification protocol， rapid triage，publicity and education, etc. Using a history-controlled approach, we analyzed acute ischemic stroke patients with intravenous thrombolysis, in pre-intervention period (April 1, 2015-July 31, 2016), trial period (August 1, 2016-October 31, 2016), and post-intervention period (November 1, 2016-September 30, 2017), according to the implementation of nursing quality improvement measures, including the general characteristics of the three groups, the time of each step in the process of thrombolysis, and the prognosis. Results: After the implementation of nursing quality improvement measures, the median door-to-needle time (DNT) was shortened from 73 minutes (interquartile range [IQR] 62-92 minutes) to 49 minutes (IQR 40-54 minutes; p<0.001) in the post-intervention period. The median onset-to-needle time (ONT) was reduced from 193 minutes (IQR 155-240 minutes) to 167 minutes (IQR 125-227 minutes; p<0.001). The proportion of patients with DNT ≤ 60 minutes was increased from 23.94% (51/213) to 86.36% (190/220; p<0.001), DNT ≤ 40 minutes was increased from 3.29% (7/213) to 25.00% (55/220; p<0.001). Median door-to-laboratory results time was decreased from 68 minutes to 56 minutes (p<0.001). There was no significant difference in the fatality rate, 90-day modified Rankin score, length of stay and hospitalization expenses between the three groups of patients (p>0.05). Conclusions: Implementation of nursing quality improvement measures in stroke nurses is an important factor in shortening the time of medication in patients with thrombolytic therapy, reducing the delay of intravenous thrombolysis in the hospital, and helping expedite patients presenting to the hospital post-stroke.